Geografi, kunnskap, vitenskap Den regionale UH-sektorens framvekst og betydning - Knudsen, Jon P.; Lauvdal, Torunn (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2019)
"This anthology explores the development of the higher education sector with respect to regional and national contexts. In Norway, the challenge of unifying a country with deeply-rooted and distinct local identities has been a cornerstone in nation-building. The political agenda pursued in developing and expanding higher education and research in Norway bears the unmistakable mark of such nation-building work. Education and research policy has been through various phases and subjected to shifting paradigms. Beginning the 1960s, higher educational institutions were established throughout the country to specifically meet regional demands for a well-educated workforce. A result of this process was that by the beginning of the 1990s, Norway had one of the world's most decentralized higher education systems, gauged in relation to population. There followed a period with a series of reforms for concentration and unification in order to increase quality and strengthen research and national competitive advantage in an age when information had become our most important resource. There have been fluctuating views on administration of the system as a whole and within the system, influenced by international trends. This does not mean that regional ambitions slackened, but they assumed other forms. The need for highly educated labor was just as great, and in addition came an increased need for greater information and collaboration between regional business interests and public institutions. In this anthology, we attempt to sketch the historical development that has characterized our higher education sector. How should we understand and explain the direction this development has taken? Which interests, drivers and actors can we identify? What consequences can we trace? To a certain extent we are also trying to look ahead on the basis of where we are now. The contributions in this anthology are from key researchers in the field, and their theoretical and empirical approaches to the topic vary. This diversity provides a nuanced image of the exciting developments within our current higher education sector, and the conditions for its future development. "